(untitled) (KULT_online, 2010)
In his habilitation work, historian Klaus Gestwa presents a study concerning giant projects of energy production, which were one of the basics of Soviet command economy. As the author argues, the political leaders were quite successful during the Fifties and Sixties in evoking technophilia and faith in progress within the population. By the beginning of the Perestroika these expectations had completely vanished. However, although the "late Soviet era" consistently failed to live up to its promises, giant hydroenergy projects are not out of political minds – foremost in the People’s Republic of China. With this work Gestwa provides a pioneer work voicing a distinct warning against the incalculable risks of such projects.